Associations Between Maternal Thyroid Function and Birth Outcomes in Chinese Mother-Child Dyads: A Retrospective Cohort Study - Chen, Geng-Dong; Pang, Ting-Ting; Lu, Xia-Fen; Li, Peng-Sheng; Zhou, Zi-Xing; Ye, Shao-Xin; Yang, Jie; Shen, Xiu-Yin; Lin, Dong-Xin; Fan, Da-Zhi; Lu, De-Mei; Liu, Zheng-Ping (Frontiers in Endocrinology, 2021)
Objective: Although research suggests a close association between maternal thyroid function and birth outcomes, no clear conclusion has been reached. We aimed to explore this potential association in a retrospective cohort study. Methods: This study included 8985 mother–child dyads. The maternal serum free tetraiodothyronine (FT4), thyroid-stimulating hormone (TSH), and thyroid peroxidase antibody (TPO Ab) concentrations and birth outcome data were reviewed from medical records. Subjects with TPO Ab concentrations of >34 and ≤34 IU/mL were classified into the TPO Ab+ and TPO Ab negativity (TPO Ab−) groups, respectively. Results: Subjects with TSH levels of 2.5–4.0 mIU/L and TPO Ab− negativity (−) had 0.65-fold lower risks of low birth weight (LBW). However, those with TSH levels>4.0 mIU/L with TPO Ab+/− had a 2.01-fold increased risk of LBW. Subclinical hypothyroidism with TPO Ab+/− was associated with a 1.94-fold higher risk of LBW. No other significant associations were observed. Conclusion: A maternal TSH level of 2.5–4.0 mIU/L lower the risk of LBW when combined with TPO Ab−, whereas increase the risk of LBW were observed in subjects with TSH >4.0 mIU/L. Subclinical hypothyroidism contributed to higher risk of LBW.